The Historic River Witham Bridge, Lincoln, UK. Issue 4 (12th July 2019) - De'Ath, Samuel Paul; Heap, Christopher B.
Abstract : River Witham Bridge in Lincoln, UK, is an underline railway bridge carrying two tracks over the River Witham and is owned by Network Rail. The bridge was listed in 1999 to recognise the historical significance of the 1848 river span, which comprises very rare tubular edge girders patented by the engineer William Fairbairn. The bridge was found to be in poor condition and have an inadequate assessed capacity for current rail traffic. To address these issues the bridge was successfully reconstructed in 2017, while the historic river span was also repaired and conserved – an essential element of the project. The conserved girders from the original river span were reinstated beneath the reconstructed bridge deck, maintaining the historic fabric and appearance of the original bridge for the benefit of future generations. The asset management, historical significance, maintenance, mitigation, reconstruction and conservation of this historic bridge are described in this paper.